Draft Annual Plan 2006-2007 Volume-I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2006)
Paddy is the main crop grown during Kharif in about 25% of the land available for agricultural purpose. The rice area is mainly restricted in Andaman District where about 12000 ha. is cultivated under paddy now after Tsunami occurred on 26th Dec 2006, about 4000 Ha has been intruded by saline water. This area is also utilized for pulses, oilseeds and vegetables in Rabi after harvest of paddy. Such crops are grown under rainfed condition due to lack of proper irrigation facilities.
Andaman and Nicobar Administration, Planning Department